THE USAGE OF THE MULTIMEDIA TECHNOLOGY IN THE FUTURE BIOLOGY TEACHERS' METHODICAL TRAINING - N.B. Grytsai (Kherson State University, 2012)
The essence of the concept "multimedia technology" is clarified, their importance in the educative process is disclosed in the article. Possibilities of the multimedia technology in biology and other subjects teaching methods in the higher educational establishment are analysed, as well as examples of the multimedia usage in the future biology teachers' methodical training are made.